New Coumarinic Azo-Derivatives of Metoclopramide and Diphenhydramine: Synthesis and In Vitro Testing for Cholinesterase Inhibitory Effect and Protection Ability Against Chlorpyrifos - AAJ, Mahmood; YS, Mustafa; M, Abdulstaar (IIUM Medical Journal Malaysia, 2014)
Introduction: This study aims to synthesize new coumarin azo compounds of metoclopramide and diphenhydramine and to evaluate their in vitro cholinesterase inhibitory effects and protection abilities against chlorpyrifos. Methods: Two series of azo coumarin compounds were synthesized. Series I compound resulted from the diazotization of metoclopramide and then coupling with coumarin and 4-methyl coumarin to give compounds 1 and 2 respectively. Series II compound resulted from the diazotization of 7-aminocoumarin and 7-amino 4-methyl coumarin and then coupling with diphenhydramine to give compounds 3 and 4 respectively. The new compounds were tested for their in vitro cholinesterase inhibitory effect and protection ability against chlorpyrifos using the modified Elman electrometric method. Results: Metoclopramide derivatives with coumarin show selectivity protection for ChE against chlorpyriphos inhibitory effect as protect BChE and increase the inhibition of the AChE, or the opposite. Conclusion: Diphenhydramine derivatives with coumarin show more protective ability for both BChE and AChE as one of them shows the maximum protection for all concentration. However, the other derivative shows different manner as the low concentrations act as metoclopramide derivatives while the high concentration act as first diphenhydramine derivative (protect both AChE and BChE).